THE ROLE OF DIGITAL MEDIA IN THE SOCIALIZATION OF CHILDREN - Rančić, Jovana S (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
The topic of the paper is the role of digital media in the process of socialization of children. Digital media are becoming an increasingly important agent of socialization, they are an indispensable part of everyday life and as such greatly influence our identity, thoughts, political beliefs, and image. Children are the most susceptible to media influence to which they are exposed. Available research conducted on this topic shows that children spend most of their free time on media content. The aim of the paper is to present some of the risks and benefits of using digital media based on a secondary analysis of the literature, but also to point out the importance of media literacy and educational competence of parents in the area of ​​protecting children from the harmful consequences of using digital media. The risks of use are not only related to the time spent with digital media, but also to the quality of the content that children choose. The presented risks of using digital media relate to violent and inappropriate content, social comparison theory, and security threats. The benefits of using digital media are mainly included in learning processes. Media literacy and media pedagogy as interdisciplinary areas are important in the formation of a critical attitude towards media discourse at an early age. Their inclusion in educational systems will contribute to the development of democratic values ​​in society and the fight against racial, religious, gender and other stereotypes. Parents’ educational competences and parental mediation are important factors in protecting children from the risks they face on digital platforms. Of the numerous types of parental mediation in controlling children’s access to digital media and the use of various applications and tools for those purposes, as an extremely effective method, it is recommended to talk about the dangers of using different media content and the joint use of digital media.